2018
DOI: 10.1038/s41598-018-34841-6
|View full text |Cite
|
Sign up to set email alerts
|

A practical protocol for measurements of spinal cord functional connectivity

Abstract: Resting state functional magnetic resonance imaging (fMRI) has been used to study human brain function for over two decades, but only recently has this technique been successfully translated to the human spinal cord. The spinal cord is structurally and functionally unique, so resting state fMRI methods developed and optimized for the brain may not be appropriate when applied to the cord. This report therefore investigates the relative impact of different acquisition and processing choices (including run length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 51 publications
6
32
0
Order By: Relevance
“…44). Therefore, although BOLD CNR is maximal when TE = T2, in practice this is not a strict requirement and is likely detrimental for spinal cord fMRI studies because maximizing BOLD CNR also maximizes signal dropout and geometric distortions 34 . These early studies characterizing BOLD CNR curves 43,44 thus support our observation of comparable GM CNR between these sequences despite substantially different echo times.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…44). Therefore, although BOLD CNR is maximal when TE = T2, in practice this is not a strict requirement and is likely detrimental for spinal cord fMRI studies because maximizing BOLD CNR also maximizes signal dropout and geometric distortions 34 . These early studies characterizing BOLD CNR curves 43,44 thus support our observation of comparable GM CNR between these sequences despite substantially different echo times.…”
Section: Discussionsupporting
confidence: 73%
“…Reduced distortions are desired in spinal cord MRI due to the small size of the cord and need to accurately register functional images to their corresponding anatomical images, so we selected an FFE sequence to mitigate geometric distortions and also satisfy specific absorption rate constraints 30 at 7T, thus facilitating the detection of resting state networks in the human spinal cord 31‐33 . We then continued this line of work and translated the FFE sequence to 3T to further evaluate the relative impact of acquisition and processing choices on the detectability of resting state spinal cord networks 34 . The FFE sequence has, however, not yet been systematically evaluated in detecting stimulus‐evoked BOLD signal changes in spinal cord fMRI.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord fMRI, however, is particularly challenging due to magnetic field inhomogeneities at bone-tissue interfaces causing imaging artifacts with conventional BOLD imaging and the high levels of physiological noise from the cardiac and respiratory cycles, which confound signal detection ( Summers et al, 2010 ). The spinal cord imaging field is gradually overcoming these challenges ( Barry et al, 2018 ), and spinal cord fMRI is now showing potential to localize areas of normal and abnormal sensorimotor function with applications in fibromyalgia, multiple sclerosis, cervical spondylotic myelopathy, and incomplete spinal cord injury ( Cadotte et al, 2012 ; Conrad et al, 2018 ; Liu et al, 2016 ; Martucci et al, 2019 ). Spinal cord fMRI combined with sensory testing may improve our ability to localize the level of spinal nerve root compromise while also providing stronger prognostic and predictive information on the capacity for functional recovery in spinal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Ozturk et al showed that T 2 *‐weighted gradient‐echo scans in the spinal cord show multiple sclerosis lesions with greater regularity compared with conventional T2‐weighted spin echo imaging . With growing interest in spinal cord functional MRI, there is also an increasing need to measure T 2 * relaxation times in healthy volunteers to carefully design more sensitive sequences for gradient‐echo‐based functional spinal cord imaging. It should also be noted that conventional, longer echo T2‐weighted imaging of the spinal cord does not demonstrate gray matter (GM)/white matter (WM) contrast to the extent that T 2 *‐weighted gradient‐echo scans do, which, if optimized for contrast, can offer a unique ability to measure both WM and GM atrophy in disease.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that conventional, longer echo T2‐weighted imaging of the spinal cord does not demonstrate gray matter (GM)/white matter (WM) contrast to the extent that T 2 *‐weighted gradient‐echo scans do, which, if optimized for contrast, can offer a unique ability to measure both WM and GM atrophy in disease. While accurately measuring the relaxation parameters T1, T2, and T 2 * is commonly performed for organs of interest at a given field strength, for T 2 * specifically, knowledge of such relaxation times could improve our assessment of lesions in multiple sclerosis and traumatic cord injury, further optimize functional MRI scanning routines, and offer new opportunities for susceptibility imaging. In the human cervical spinal cord, measurements of T1 and T2 and R 2 * (1/T 2 *) have been reported at 3T, and measurements of T1, T2, and T 2 * were recently made at 7T .…”
Section: Introductionmentioning
confidence: 99%